GAMBARAN PENDIDIKAN LANJUT USIA KOMPLEK PERUMAHAN CENDANA KELURAHAN ANDALAS KECAMATAN PADANG TIMUR DALAM MEWUJUDKAN KESEJAHTERAAN SOSIAL - Murlis Murlis (Ensiklopedia Education Review, 2020)
The social welfare of the elderly is an action as an effort to fulfill the needs of the community, especially the elderly who are unable to carry out their social functions, namely by providing assistance and sponsorship services. Thus, it is hoped that the elderly can improve their welfare so that they can live properly. According to Government Regulation Number 43 of 2004, what is meant by efforts to improve the social welfare of the elderly is a series of activities carried out in a coordinated manner between the government and the community to empower the elderly so that the elderly can continue to carry out their social functions and play an active role naturally in the life of the community, nation and state. Law of the Republic of Indonesia Number 13 of 1998 concerning the Welfare of the Elderly states that efforts to improve the social welfare of the elderly are carried out on the basis of faith and devotion to God Almighty. Efforts to improve social welfare are aimed at extending the life expectancy and productive period, creating independence and welfare, maintaining the cultural value system and kinship of the Indonesian nation, and getting closer to God Almighty.